Legal deadlock in the company: ways to resolve shareholder disputes - Dilytė, Simona; Juodikis, Domantas (Vilnius University Open Series, 2024)
This paper draws on foreign doctrine and Lithuanian case law to present the concept of legal deadlock, analyses the judicial methods of resolving legal deadlock, and presents the most common contractual methods of resolving deadlock in shareholders’ agreements. The relationship between an option and a preliminary agreement and the criteria for distinguishing between them are described on the basis of Lithuanian court interpretations. It also analyses the operation of the freedom of contract principle within the framework of shareholders’ agreements, based on Lithuanian case law and compared with the position of the Italian courts. It also describes the problems of the practicability of the option, taking into account the categories of inviolability of property and public interest. The analysis of these aspects leads to the conclusion that an option contract can be enforced in kind, but that the courts do not provide effective practical mechanisms to force a party to sign the contract.
Keywords: deadlock; shareholders’ agreement; option; freedom of contract; enforceability